Reactualizing Islamic Inheritance Law: Munawir Sjadzali’s Perspective on Gender Equality in Indonesia - Arief Rahman Riyanda (Jurnal El-Thawalib, 2026)
This research analyzes Munawir Sjadzali’s reactualization of Islamic inheritance law in Indonesia, motivated by the tension between the 2:1 ratio and modern roles of women. Method: qualitative library research. Approaches: normative-philosophical and sociological. Primary data: Sjadzali’s "Hukum Waris Islam di Indonesia," "Ijtihad Kemanusiaan," and "Kontekstualisasi Ajaran Islam." Secondary data: journals, theses, and Yogyakarta Religious Court Decision No. 207/Pdt.G/2023/PA.Yk. Data collection: documentation. Data analysis: content analysis. Results indicate the 1:1 ratio proposal addresses Muslims' "ambivalent attitude" in using hibah for justice. This ijtihad, based on Maslahah theory and Umar bin Khattab's precedents, establishes an adaptive "Indonesian Fiqh." Its relevance is evidenced by judicial practices accommodating equal distribution via islah. It recommends reforming the Compilation of Islamic Law (KHI).